Job stress, work-to- family conflict and social support in the education industry / Nurmazlina Mohd Isa, Hardev Kaur Latchimanan Singh and Rozalli Hashim - Mohd Isa, Nurmazlina; Latchimanan Singh, Hardev Kaur; Hashim, Rozalli (Faculty of Administrative Science & Policy Studies (FASPS), Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
This paper is based on specific research that has been conducted on work-to-family conflict among teachers in specific schools in Malaysia . Teachers are agents that are important in delivering quality education to students. Teachers contribute to developing high quality in education and human capital to the nation. However, teachers face considerable stress and conflict in carrying out their tasks effectively that lead to work family conflict. This study will examine three main components of job stress that lead to work family conflict which is role overload, role ambiguity and role conflict and also the role played by social support in reducing work-family conflict. The findings of the study are yet to be disclosed, but this paper is heavily based on the research conducted.